THE EFFECT OF CORPORATE GOVERNANCE (CG), PRODUCTION EFFECTIVENESS (PE), AND ENVIRONMENTAL SUSTAINABILITY (ES) ON COMPANY VALUE (CV) - Yulias, Messia; Megawati Oktorina (Media Riset Akuntansi, Auditing & Informasi, 2025)
As a curious in finding out the variables essence on firm value amongst business conditions of global struggle in the influence of Covid-19. The aim of study is to prove whether Good Corporate Governance (GCG) as the ideology and foundation to actualize the production of business will effect to firm value, in which mediated with the effectiveness of production and moderated with the environmental sustainability compliance due to business sector. The research sample is the sector of primary consumer goods of the IDX during 2018-2020. And it special highlight to only those companies whose running the production, excluded distributors nor retailers. The research through purposive sampling, which collecting 93 data by running data system with macro v4.1 PROCESS. The results of empirical research reveal GCG increases the firm value. Though, GCG does not impact to production effectiveness. While production effectiveness has a positive impact to firm value but it does not impact to the mediation relationship between GCG and firm value. The results of the compliance of environmental sustainability is able in moderating the impact of GCG to firm value.